“PRZECIW SWEMU ZWYCZAJOWI NOWINKAMI CIĘ BAWIĘ” (“AGAINST MY USUAL HABIT, I AMUSE YOU WITH NOVELTIES”). EMILIA WRÓBLEWSKA’S LETTERS TO HER SON TADEUSZ. REFLECTIONS ON THE MARGINS OF THE DIGITAL EDITION OF HER DIARIES - Kozyra, Agnieszka (Prace Polonistyczne, 2025)
The correspondence of Emilia Wróblewska, née Beniowska (1830–1886), to her son Tadeusz (specifically, 29 letters sent to the Warsaw Citadel in the early 1880s) has until recently been used mainly as a source of knowledge about the addressee and other male members of the Beniowski and Wróblewski families. However, according to the author of this article and other researchers of Emilia’s manuscripts, Wróblewska’s rich legacy warrants closer study in its own right. The egodocuments illuminate the ethos of a Polish mother (as patriot, Christian, teacher), while also serving as a testimony to women’s literary, social, and educational activities in the difficult period following two national uprisings. Despite holding traditional values and somewhat anachronistic views, Wróblewska, a noblewoman from Vilnius, emancipated herself in a way in spite of herself, which is expressed not only through some of her writings but, above all, through her multifaceted activity. Preserving and presenting Wróblewska’s “self-testimony” as faithfully as possible is crucial, yet adapting the source material to meet the needs of the modern reader is equally important. Digital scholarly editing offers some solution to both challenges, as demonstrated by the team behind the electronic edition of Wróblewska’s diaries. This approach allows researchers to provide the text in three formats (high-quality scans of the original manuscripts, transliteration, and transcription), along with linguistic and factual annotations and TEI coding. In this way, Wróblewska’s legacy can reach a wider audience and her-story can be revived from the depths of history.